2013
DOI: 10.5713/ajas.2012.12469
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Korean Native Chicken Lines Using Fifteen Selected Microsatellite Markers

Abstract: In order to evaluate the genetic diversity and discrimination among five Korean native chicken lines, a total of 86 individuals were genotyped using 150 microsatellite (MS) markers, and 15 highly polymorphic MS markers were selected. Based on the highest value of the number of alleles, the expected heterozygosity (He) and polymorphic information content (PIC) for the selected markers ranged from 6 to 12, 0.466 to 0.852, 0.709 to 0.882 and 0.648 to 0.865, respectively. Using these markers, the calculated geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
29
6
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 25 publications
6
29
6
5
Order By: Relevance
“…People thought that native chicken meat has better taste and meat quality than that of commercial broilers. In Korea, native chicken is preferred by Korean consumers because Korean native chicken (KNC) has less fat and better protein content, even though its price is 2 to 3 times higher than that of commercial broilers (Sang et al, 2006;Hoque et al, 2011;Seo et al, 2013). Therefore, improving both meat quality and quantity in Korean native chicken will be great challenge for poultry industry.…”
Section: Introductionmentioning
confidence: 99%
“…People thought that native chicken meat has better taste and meat quality than that of commercial broilers. In Korea, native chicken is preferred by Korean consumers because Korean native chicken (KNC) has less fat and better protein content, even though its price is 2 to 3 times higher than that of commercial broilers (Sang et al, 2006;Hoque et al, 2011;Seo et al, 2013). Therefore, improving both meat quality and quantity in Korean native chicken will be great challenge for poultry industry.…”
Section: Introductionmentioning
confidence: 99%
“…D-loop control region은 non-coding region으로 기능 적인 역할을 담당하지 않고 변이가 다른 영역보다 두드러지 기 때문에 많이 활용되었고, COI 유전자는 주로 조류의 품종 구분 연구에 주로 활용되어 왔다 (Hebert et al, 2003 (Cheng and Crittenden, 1994;Kaya and Yildz, 2008 (Kim et al, 2004;Cahyadi et al, 2013). 특히, MC1R 유전자는 다양한 축종에서 피모색 과 관련된 유전변이를 찾고자 연구가 수행되어져 왔다 (Kerje et al, 2003;Maklund et al, 1996;Vage et al, 1999) Heo 등 (2011) Hoque et al (2013), Kim et al (2014) c.212C>T Nonsynonymous Heo et al (2011, Jin et al (2014) c.274A>G…”
unclassified
“…Nonsynonymous Heo et al (2011), Hoque et al (2013, Park et al (2013), Jin et al (2014), Kim et al (2014) c.636G>A Synonymous Park et al (2013) c.637T>C Synonymous Park et al (2013) Variation in (Seo et al, 2015a;Wallis et al, 2004). 또한 방대한 re-sequencing data 를 이용해서 60K, 600K 등의 high-density(HD) SNP chip이 개발되어 많은 유전자 마커의 정보를 획득할 수 있게 되었 다 (Groenen et al, 2011;Kranis et al, 2013 …”
unclassified
“…Recent studies reported inter relationship between breed or strain of chicken and its effect on egg quality (Monira et al, 2003;Khawaja et al, 2013;Kabir et al, 2014) Korean native chicken (KNC), a domestic breed of Korea, have been studied to improve their production previously (Seo et al, 2013;Choi et al, 2015). However, published data on egg quality parameters and genetic effects of strains of Korean native chicken have barely been discussed.…”
Section: Introductionmentioning
confidence: 99%